Diagnostic value of presepsin in odontogenic infection: a retrospective study - Eun-Sung Kang; Jae-Hoon Lee (SpringerOpen, 2022)
Abstract Background Most head and neck infections originate from odontogenic causes; therefore, it is important to determine the severity of odontogenic infections. Since severe infection can cause sepsis, a systemic examination should be performed when evaluating a patient with odontogenic infection. C-reactive protein (CRP), white blood cell count (WBC), procalcitonin (PCT), and presepsin (PSEP) can be used to evaluate the severity of inflammatory status and sepsis in patients in the early stages of visiting the emergency room. Moreover, sepsis can be diagnosed based on the systemic inflammatory response syndrome (SIRS) classification. In relation to PSEP, significant study results on sepsis have been reported in other organ infections. However, there has been no progress in odontogenic infection; therefore, this study aimed to determine the diagnostic value of sepsis derived from odontogenic infection. Methods This study was conducted from March 2021 to October 2021 on 43 patients admitted to the Department of Oral and Maxillofacial Surgery, Dankook University Hospital, in the emergency room for odontogenic infection. All patients underwent vital sign assessment and diagnostic tests (CRP, WBC, PCT, PSEP) in the emergency room. Sepsis was classified according to the SIRS criteria, and CRP, WBC, PCT, and PSEP levels were measured. The Statistical Package for the Social Sciences was used for statistical analyses. Results The results of this study showed a moderately positive correlation between CRP and PCT, CRP and PSEP, and CT and PSEP levels. In addition, PCT and PSEP levels showed a positive correlation with sepsis. The odds ratios of sepsis and PCT and sepsis and PSEP were statistically significant. The optimal cut-off values obtained through the receiver operating characteristic curve were 0.24 and 671.5 for PCT and PSEP, respectively. Finally, there were positive correlations between CRP level and length of stay, WBC and Flynn scores, PCT level and Flynn scores, PCT level and length of stay, and PSEP level and length of stay. Conclusion WBC and CRP and PCT levels have been used in the past to determine the severity of infection and sepsis in patients with odontogenic infection, but PSEP was also found to have diagnostic value in this study. According to this study, a PSEP level of 671.5 pg/ml or higher for odontogenic infection can be considered an abnormal level.